TERRITORIAL STRUCTURE AND REGIONAL GOVERMANCE IN EASTERN EUROPE: A COMPARATIVE ANALYSIS - Панченко, Т.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
The article deals with the problems of  a comparative analysis of the territorial structure of 26 countries, which partially or completely belong to Eastern Europe, to assess the results of the administrative-territorial reform and created institutions of regional democracy. Based on a comparative analysis it is presented the typology of the countries of Eastern Europe, which allows us to estimate the prospects of regional democracy in the region.